Se o auees por ydoneo e perteencente: a propósito da atividade dos tabeliães de Lisboa nos séculos XIV e XV - Cunha, Cristina (2018)
In Portugal the medieval notary public has been thesubject of study by several authors in recent years.However, the discussion around the process involvingthe exercise of this activity is still insufficient. Basedon royal legislation, we will approach the medievalPortuguese notarial public reality through thepresentation of some practical examples. The focusof this paper is not the study of the Lisbon notarypublic, but the reflection on some aspects that involvedthe exercise of this activity, from the obligation ofthe examination to the elaboration of the notes andregisters. From a diplom of King D. Fernando (1367-83), preserved in the Arquivo Municipal de Lisboa andcopied in a codex known as Livro dos pregos, whichwas published in 2016, we present some ideas onthe subject taking also into account complementaryinformation evident in several documents of theparliament (documentos das Cortes) and of the RoyalChancery also copied in the same codex.